Satisfaction, self-confidence and self-efficacy in the use of clinical simulations: comparisons between health undergraduates and professionals - Viviane Christine dos Reis Alves Almeida; Jaqueline Costa Lima; Gímerson Erick Ferreira; João Lucas Campos de Oliveira; Jocilene de Carvalho Miraveti; Mara Regina Rosa Ribeiro (Rev Rene)
Objective: to analyze the levels of satisfaction, self-confidence, and self-efficacy in clinical simulations among health undergraduates and professionals. Methods: cross-sectional study based on Design Science Research Methodology, with 156 health professionals and 149 health undergraduates who participated in an educational session about personal protective equipment use during the COVID-19 pandemic, mediated by Rapid-Cycle Deliberate Practice. Participants responded to a social and work-related questionnaire and to validated scales. For descriptive analysis of independent samples, Chi-squared test and Student's t were used considering p<0.05 as significant. Results: we found generally high satisfaction levels (mean ± standard deviation: 4.72±0.58), self-confidence (4.44±0.78), and self-efficacy (4.03±1.17) for favorable items. There were significant statistical differences in seven items in the scale of satisfaction and self-confidence with learning in students, and in six items of the general self-efficacy scale, with p<0.05. Conclusion: undergraduates showed higher means of satisfaction and self-confidence with learning, while professionals had higher means of self-efficacy. These results can collaborate for the continuity of clinical simulation practices, increasing procedural safety and quality. Contributions to practice: the results show that the activities had a positive contribution, increasing learning opportunities and practical experiences that reflect on the excellence of the routine.